Acidification of Alperujo Paste Prevents Off‐Odors During Their Storage in Open Air. (13th November 2012) - Ruiz‐Méndez, M. V.; Romero, C.; Medina, E.; García, A.; de Castro, A.; Brenes, M.
Abstract: Alperujo is the main paste produced by the olive oil industry that must be stored in big open air ponds for months before pomace olive oil is extracted. During this period, malodorous 4‐ethylphenol is formed, and it represents a big environmental problem for the oil extracting factories. The aim of this investigation was to prevent the formation of this substance by acidification of the fresh paste. Several batches of fresh Alperujo were stored in 100‐L plastic containers for 6 months without pH control and acidified up to pH 2 or 3. Acidification inhibited the formation of 4‐ethylphenol as well as the growth of yeasts. By contrast, acidification of the paste did not affect oil acidity, triterpenic acid concentration, waxes or fatty acid composition. An increase in hydroxytyrosol of the aqueous phase of Alperujo was also observed because of hydroxytyrosol glucoside hydrolysis. The results indicated that acidification of Alperujo during storage under open air conditions reduced the formation of 4‐ethylphenol, thereby diminishing the environmental impact of the pomace olive oil production.